The foreign worker and the German labor movement : xenophobia and solidarity in the coal fields of the Ruhr, 1871 - 1914 - Kulczycki, John J., 1941- 1941- (Berg, 1994)
The rural origins of the Polish migrants and their traditional Catholic religious beliefs led most observers, including their fellow workers as well as recent historians, to view them as obstacles to the labor movement and resistant to working-class consciousness. Based on extensive research in archives in Poland and Germany, this book documents a very different history. Throughout his rigorous examination of the major strikes and developments within the labor movement in the Ruhr, including the mass strikes of 1889, 1905 and 1912 and the so-called "Polish Revolt" of 1899, the author argues that Polish militancy generally exceeded that of native miners and calls into question the standard view of the Polish workers' relationship to the labor movement. This revisionist book begs a reconsideration of the role that foreign labor plays in modern industrial societies.